High-power inductive coupler with a high-voltage DC blocker. (1st August 2022) - Kaizer, B.; Zchut, T.; Weissman, L.; Perry, A.; Eizenshtat, M.; Gavish, I.; Rodnizki, J.; Polikarpov, I.; Farber, E.
Abstract: The authors of this study developed a high-power inductive coupler with a high-voltage DC blocker that is capable of delivering up to 100 kW of CW RF power at 176 MHz and 4 kV DC. The high-power indictive coupler was developed at the Soreq Nuclear Research Center for the radio-frequency quadrupole of the Soreq Applied Research Accelerator Facility. The purpose of the DC blocker is to enable the application of high-voltage DC bias to the inner conductors of the couplers in order to prevent the multipacting phenomena. A new, mechanically and thermally improved, version of the RF coupler is designed and implemented in conjunction with the DC blocker. The underlying design principles, indigenous development, and results of tests of the coupler are presented here.